1975
DOI: 10.1007/bf00383865
|View full text |Cite
|
Sign up to set email alerts
|

Compositional changes in developing rape seed (Brassica napus L.)

Abstract: The growth and composition of siliquas and seeds of oilseed rape was followed over 12 weeks from shortly after anthesis to maturity. Each plant produced 220 siliquas, this number being constant throughout development. Seed numbers per siliqua fell from 19 to 9 by week 5 and declined to 7 at maturity. Hull(1) and seed growth followed a sigmoid pattern, but were not in phase. Seed development could be divided into 3 phases: In Phase 1, seed weight was low and starch and ethanol soluble compounds accounted for 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
86
1
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 17 publications
9
86
1
1
Order By: Relevance
“…This is in agreement with previous studies on B. napus seed development where the authors concluded that the aqueous soluble fraction increased to a maximum at 5 WAF and then declined (Norton and Harris, 1975). After this period, protein content increased dramatically, reaching approximately 10% of fresh seed weight at 6 WAF, also in agreement with a previous report (Norton and Harris, 1975). Measurements of seed fresh weight and protein content at five different stages indicate that selected time points are representative of the seed-filling phase of development.…”
Section: Characterization Of Developing B Napus Seedsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with previous studies on B. napus seed development where the authors concluded that the aqueous soluble fraction increased to a maximum at 5 WAF and then declined (Norton and Harris, 1975). After this period, protein content increased dramatically, reaching approximately 10% of fresh seed weight at 6 WAF, also in agreement with a previous report (Norton and Harris, 1975). Measurements of seed fresh weight and protein content at five different stages indicate that selected time points are representative of the seed-filling phase of development.…”
Section: Characterization Of Developing B Napus Seedsupporting
confidence: 93%
“…B. napus seeds produce oil and protein as the main storage compounds out of the three principal storage reserves (proteins, oil [triacylglycerols], and carbohydrates [starch]) found in plant seeds (Norton and Harris, 1975;Murphy et al, 1989;King et al, 1997;Schwender and Ohlrogge, 2002). These compounds support early seedling growth, and in nature the relative proportions of these compounds vary dramatically among different plant seeds.…”
mentioning
confidence: 99%
“…Rapeseeds contains about 40% to 45% (w/w) TAG, and protein is the second largest principal storage component (Norton and Harris, 1975;Gunstone, 2001). Therefore, increasing the weight fraction of oil at the expense of protein is a promising strategy to improve rapeseed and deserves theoretical exploration on the basis of constraint-based models of the central metabolism of developing seeds.…”
mentioning
confidence: 99%
“…For example, soybean (Glycine max) seed contains approximately 40% protein and 20% oil (Hill and Breidenbach, 1974;Ohlrogge and Kuo, 1984). In contrast, seed of oilseed rape (Brassica napus; also called rapeseed or canola) contains approximately 15% protein and 40% oil (Norton and Harris, 1975). To gain insight into the complex process of seed development, identification of genes and proteins and their dynamic expression profiles during seed filling are beginning to provide a framework for more indepth comparative studies.…”
mentioning
confidence: 99%